The Effects of Using Plaque-Disclosing Tablets on the Removal of Plaque and Gingival Status of Orthodontic Patients - Mehmet Ali Yavan; Sayad Kocahan; Serhat Özdemir; Oral Sökücü (Galenos Yayinevi, 2019)
Objective:The aim of this study was to investigate the effects of using plaque-disclosing tablets (PDTs) on the plaque and gingival index scores of patients wearing fixed orthodontic appliances.Methods:In group A (n=16), the subjects were motivated by conventional oral hygiene instructions, including verbal information about tooth brushing. The patients in group B (n=17) were motivated using PDTs used in the dentists' office to show the locations of biofilms in addition to the instructions given to group A. Both the chairside demonstration performed in group B and the at-home use of disclosing tablets were undertaken by those in group C (n=15). The periodontal parameters were recorded before applying the fixed appliance (T0) and after the first (T1) and third (T2) months.Results:The plaque index (PI) scores of group C were significantly lower (p<0.05), when compared to groups A and B, after the first (T1) and third months (T2); however, no significant differences (p>0.05) were found between groups A and B. The gingival status of group C did not change significantly (p>0.05) over the three months and was statistically lower when compared to groups A and B.Conclusion:The use of PDTs at home may enhance the plaque removal efficiency and gingival health stability, by facilitating self-examination.